1996
DOI: 10.1111/j.1438-8677.1996.tb00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Evidence for Xylem‐Mediated Water Transport and High Transpiration in Agrobacterium tumefaciens‐Induced Tumors of Ricinus communis*

Abstract: Abstrad: Tumors induced by the wild-type strain C58 of Agrobacterium tumefaciens in hypocotyls of Ricinus communisL.were investigated structurally and functionally with respect to xylem differentiation, cuticle and stomata development, water pathway and transpiration. Clearing of tissue with lactic acid and staining with lacmoid revealed a continuation of stem xylem into differentiated bundles in the tumor. Under the influence of tumors the host xylem below the tumors increased considerably in size. Transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Residual epidermis, characterized by continuously widely open stomata, occurred only at the borders of the host stem. Schurr et al (1996) showed that similar changes in the enlarged tumor surface substantially increased transpiration to about 15 and 7.5 times higher at the tumor surface compared with host leaves and leaves of noninfected castor bean plants, respectively. Therefore, the combination of a decrease in vessel diameter in the host and an increased surface of the tumor, both induced by ethylene, ensures water-supply priority to fast-growing crown galls.…”
Section: Discussionmentioning
confidence: 93%
“…Residual epidermis, characterized by continuously widely open stomata, occurred only at the borders of the host stem. Schurr et al (1996) showed that similar changes in the enlarged tumor surface substantially increased transpiration to about 15 and 7.5 times higher at the tumor surface compared with host leaves and leaves of noninfected castor bean plants, respectively. Therefore, the combination of a decrease in vessel diameter in the host and an increased surface of the tumor, both induced by ethylene, ensures water-supply priority to fast-growing crown galls.…”
Section: Discussionmentioning
confidence: 93%
“…Reasons for the reduction in species abundance in summer might be higher temperatures and drought stress. It is known from the model plant Arabidopsis (63,64) and Ricinus communis (65) that crown gall growth is affected by drought stress. In graft unions without a crown gall, the diversity of the bacterial species was only marginally affected by the season.…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium-induced plant tumors show increased water loss, resulting in a redirection of water flow and nutrient transport necessary for tumor development (Schurr et al, 1996;Wächter et al, 2003). On the contrary, increased water loss causes tissue desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors display a ruptured surface that is devoid of a cuticle covered epidermal cell layer; as a result tumors exhibit an increased water loss (Schurr et al, 1996). Usually, this is prevented by specialized cell types that contain substantial amounts of aliphatic polymers like cutin or suberin: Cutin is a major component of the cuticle that covers all aerial primary organs and forms the interface between plant and atmosphere.…”
mentioning
confidence: 99%